An exploratory study of entrepreneurs in impoverished communities: when institutional factors and individual characteristics result in non-productive entrepreneurship. Issue 1 (1st January 2020) - Matos, Stelvia; Hall, Jeremy
ABSTRACT: It is widely acknowledged that entrepreneurship can help the poor escape poverty. However, while many people in impoverished regions engage in entrepreneurial activities, many fail to develop successful businesses. This paper examines why impoverished people may choose to engage in entrepreneurship, the characteristics that shape their entrepreneurial behaviour and the struggles they face. We draw on the entrepreneurship literature that suggests institutional factors and individual characteristics shape new venture development. Following an inductive methodological approach utilizing a survey, interviews and focus groups collected from an impoverished community in Brazil, we explore entrepreneurial behaviour focused on perceived alertness, utilization of social networks, formal business registration and participation in training. We found that temporal myopia, misjudgement of their abilities, and counter-productive use of their social networks result in non-productive entrepreneurship. We contribute theoretically by suggesting that, in addition to productive, unproductive and destructive entrepreneurial outcomes shaped by institutions, non-productive entrepreneurship is also a prevalent problem, but is heavily shaped by the interactions between individual characteristics and the institutional environment.